Bonded histories genealogies of labor servitude in colonial India - Prakash, Gyan 1952- (Cambridge South Asian studies, 1990)
To the modern world, the notions that freedom is an innate condition of human beings and that money possesses the power to bind people appear as natural facts. Bonded Histories traces the historical processes by which these notions became established as dominant discourses in India during colonial rule and continued into post-colonial India. Gyan Prakash locates the formulation of these discourses in the history of bonded labour in southern Bihar. He focuses on the emergence and subsequent transformation of the relationship of reciprocal power and dependence between landlords and labourers. The author explores the way in which these transformations were connected with broader shifts in the political economy of this part of the subcontinent; with the changing structures of agricultural production, land tenure and revenue demand; with local social hierarchies and the ideology of castes; and with Hindu cosmologies, spirit cults and their articulation in ritual practices